2009
DOI: 10.1890/07-1208.1
|View full text |Cite
|
Sign up to set email alerts
|

Disperser limitation and recruitment of an endemic African tree in a fragmented landscape

Abstract: Forest fragmentation may have positive or negative effects on tropical tree populations. Our earlier study of an endemic African tree, Leptonychia usambarensis (Sterculiaceae), in the East Usambara Mountains of Tanzania, found poorer recruitment of seedlings and juveniles in small fragments compared to continuous forest, and concomitant reduction of seed-dispersal agents and seed dispersal. However, the possibility that other biotic or abiotic consequences of the fragmentation process contribute to diminished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 65 publications
(118 reference statements)
5
75
1
1
Order By: Relevance
“…Our findings highlight that global declines in vertebrate populations (14-17) could significantly impact forest regeneration through reducing seed dispersal. While Guam represents an extreme case of complete disperser loss, leading to gap seedling richness being approximately halved and seedling turnover among gaps being doubled, other studies have demonstrated that partial loss of dispersers can reduce seedling diversity and disproportionally alter species abundances (20,23,45), particularly of light-demanding pioneer species (22,46). While we have to wait to see how gap dynamics play out in the presence and absence of dispersers on these islands, our findings show that global vertebrate losses have the potential to profoundly alter tropical forest composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings highlight that global declines in vertebrate populations (14-17) could significantly impact forest regeneration through reducing seed dispersal. While Guam represents an extreme case of complete disperser loss, leading to gap seedling richness being approximately halved and seedling turnover among gaps being doubled, other studies have demonstrated that partial loss of dispersers can reduce seedling diversity and disproportionally alter species abundances (20,23,45), particularly of light-demanding pioneer species (22,46). While we have to wait to see how gap dynamics play out in the presence and absence of dispersers on these islands, our findings show that global vertebrate losses have the potential to profoundly alter tropical forest composition.…”
Section: Resultsmentioning
confidence: 99%
“…Key issues here are that even high hunting pressure has not led to the complete loss of vertebrate dispersers (e.g., ref. 14); hunting also removes vertebrate seed predators and seedling browsers (20,22,23), making it difficult to isolate an effect of seed disperser loss alone; and the treatment of interest (removal of vertebrate dispersers) can be confounded with other site differences. Hunting pressure, for example, is often higher in areas without formal conservation protection, meaning these areas experience additional human pressures that affect tree populations, such as forest fragmentation and tree harvesting (14,20,24,25).…”
mentioning
confidence: 99%
“…However, we believe it is essential to conduct similar studies in a diversity of fragmented landscapes, as well as with a broader diversity of plant functional groups, to better predict the consequences of fragmentation on plant recruitment (Flinn and Vellend 2005). To date dispersal mechanisms have received the most attention, with studies suggesting less dispersal limitation for wind-and vertebrate-dispersed species (Flinn and Vellend 2005, Muscarella and Fleming 2007, Cordeiro et al 2009). Furthermore, most of the attention in tropical systems has focused on tree species (e.g., Norden et al 2009), despite the fact that understory plants represent up to 25% of the plant diversity in tropical forests (Gentry and Emmons 1987).…”
Section: Effects Of Abiotic and Biotic Factors On Safe-site Limitationmentioning
confidence: 99%
“…Zelikova & Breed (2008) stated that, when mainly a small number of species in an environment perform the removal of seeds, the removal rate might decrease, by the loss of these species or their density reduction. According to Cordeiro et al (2009), the loss of seed disperser organisms can endanger the plant species that depend on these for the dispersion process, or for the seeds germination, hence the establishment of new individuals and populations of this species. Thus the A. laevigata foraging becomes important for S. lycocarpum seed dispersal, even in small proportions and the short distances.…”
Section: Resultsmentioning
confidence: 99%